Comparison of Citrate and Heparin for Continuous Renal Replacement Therapy in Pediatric Intensive Units - Edin Botan; Ayşen Durak; Emrah Gün; Anar Gurbanov; Burak Balaban; Fevzi Kahveci; Hasan Özen; Hacer Uçmak; Ali Genco Gençay; Tanıl Kendirli (Galenos Yayinevi, 2023)
Introduction:The choice of anticoagulation in continuous renal replacement therapy (CRRT) is very important for circuit life and bleeding complications. The primary outcome of our study was circuit lifespan. Secondary outcomes, we aimed to identify metabolic complications.Methods:This retrospective study was conducted in our pediatric intensive care unit between November 2019 and March 2021.Results:The study included 35 patients, 19 with regional citrate anticoagulation (RCA) and 16 with heparin anticoagulation (HA). The patient's pediatric risk of mortality III score was similar in both groups (p=0.76); also, p-SOFA score was higher in the RCA group and was significant [(HA: 6.43±5.24, RCA: 10.21±3.96, p=0.024)]. 100 hemofilter were used in all therapies (total CRRT times 4115.50 h), 43 in HA and 57 in the RCA group. Median circuit life and total CRRT duration were longer for RCA [(33.0; 3.0-168.0) (30.5; 9.0-520.0) (14.0; 0.75-285.0) (94.0; 11.0-394.0) (p=0.043\0.021)] than for HA. Hypocalcemia was detected 9/19 in the RCA and 4/16 in the HA (p=0.021). HA was preferred in 3 patients and RCA in 4 patients who needed ECMO simultaneously with CRRT. The most common reason for circuit change in RCA groups is patient-related and clotting in the heparin group. Mortality rates were not the same in both groups (p=0.012).Conclusion:Citrate 18/0 has better safety and efficacy with a long filter life and easily manageable systemic complications. In addition, anticoagulation with RCA may be preferred in patients monitored with ECMO and in need of CRRT.